Functional Imaging and Assessment of Antitumor Activity in Systemic Therapy for Hepatocellular Carcinoma - Kambadakone, Avinash; Baliyan, Vinit; Zhu, Andrew X. (Seminars in Liver Disease, 2017)
Increasing use of novel systemic treatment options in the management of patients with advanced hepatocellular carcinoma (HCC) such as antiangiogenic and molecular-targeted therapies, poses unique challenges for effective treatment monitoring and efficacy assessment. The traditional morphological criteria such as response evaluation criteria in solid tumor (RECIST) rely on changes in tumor size to determine treatment efficacy. However, these criteria based on tumor morphology may not be suitable to monitor response to newer targeted therapies as early functional changes induced by these drugs precede changes in tumor size. Modifications of these morphological criteria that determine response based on tumor enhancement characteristics such as modified RECIST (mRECIST) will potentially allow improved determination of treatment response pending validation from prospective trials. Advanced functional imaging techniques such as perfusion imaging (computed tomography/magnetic resonance imaging [CT/MRI]), diffusion weighted MRI (DW-MRI) and positron emission tomography (PET/CT and PET/MRI) are being increasingly used as surrogate imaging biomarkers to provide superior assessment of changes in tumor physiology. Growing emphasis on precision oncological care tailored to specific tumor type and individual patients renders the use of these newer imaging modalities more pertinent and timely. In this review, the authors discuss the role of various imaging techniques and response assessment criteria in the evaluation of systemic therapy for advanced HCC with focus on functional imaging tools.
Keywords: hepatocellular carcinoma; computed tomography; magnetic resonance imaging; systemic therapy; response assessment; RECIST; mRECIST